2022
DOI: 10.1155/2022/9299574
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Ginsenosides: An Update on the Molecular Mechanisms

Abstract: Ginsenosides are a class of active components extracted from ginseng plants (such as Panax ginseng, Panax quinquefolium, and Panax notoginseng). Ginsenosides have significant protective effects on the nervous system, cardiovascular system, and immune system, so they have been widely used in the treatment of related diseases. Entry of a variety of endogenous or exogenous harmful substances into the body can lead to an imbalance between the antioxidant defense system and reactive oxygen species, thus producing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 118 publications
(117 reference statements)
0
27
0
Order By: Relevance
“…Ginsenosides have a variety of pharmacological activities, including preventing neurological diseases, increasing immune function, delaying aging, and improving sleep (Kim et al, 2018 ; Jin et al, 2021 ). Although the importance and yield of ginsenosides have been widely studied, the yield of ginsenosides remains low (Zhang et al, 2021a ; He et al, 2022 ). Therefore, it is urgent to optimize ginseng cultivation techniques and increase ginsenoside yields to meet medicinal needs.…”
Section: Introductionmentioning
confidence: 99%
“…Ginsenosides have a variety of pharmacological activities, including preventing neurological diseases, increasing immune function, delaying aging, and improving sleep (Kim et al, 2018 ; Jin et al, 2021 ). Although the importance and yield of ginsenosides have been widely studied, the yield of ginsenosides remains low (Zhang et al, 2021a ; He et al, 2022 ). Therefore, it is urgent to optimize ginseng cultivation techniques and increase ginsenoside yields to meet medicinal needs.…”
Section: Introductionmentioning
confidence: 99%
“…PNS protected HUVECs from AGE-induced injury by upregulating the expression of SIRT1 and increasing the SOD level [138]. Keap-1/Nrf2/HO-1 pathway mediated antioxidant activity of 20(S)-Rg3 and 20(R)-Rg3 in H9C2 cells [139]. Similar functions were presented in Panax ginseng C.A.…”
Section: Panax Notoginseng and Panax Ginsengmentioning
confidence: 53%
“…( Hou et al, 2021 ; Liu G. et al, 2022 ). Modern pharmacology has shown that ginsenosides have neuroprotective ( Zarneshan et al, 2022 ), anti-aging ( Meng et al, 2022 ), anti-oxidant ( He et al, 2022 ), anti-inflammatory ( Xu et al, 2022 ) and anti-cancer ( Zhao L. et al, 2022 ) effects. Numerous ginsenosides has been reported have various anti-cancer activity.…”
Section: Introductionmentioning
confidence: 99%